ANALISIS KEGIATAN P5 PADA KURIKULUM MERDEKA DALAM MEMINIMALISIR BULLYING - Satriani; Ekawati, Mutmainna; Bachtiar, Tauhidah; H, Anita; Nurlaeliana; Sartinayanti (Universitas Cokroaminoto Palopo, 2025)
The aim of this research is to examine the P5 activities that have been implemented and the influence of P5 activities in minimizing bullying behavior at MTs DDI Mangempang. This research uses a descriptive qualitative approach. The data collected in this research consists of: a) primary data, namely information obtained directly from the original source through various data collection procedures and techniques, such as interviews, observation and documentation; b) secondary data, namely information obtained from indirect sources, which generally take the form of official documents or archives, journals or books. The implementation of P5 is one of the solutions implemented at MTs DDI Mangempang in order to prevent bullying behavior by providing understanding and knowledge about the meaning of bullying and functioning as a strong supporter in shaping student character and increasing self-confidence and courage in students